The impacts of supermarkets and hypermarkets from the perspectives of fresh fruit and vegetable (FFV) wholesalers and retailers. - Abdullah, Amin Mahir; Mohamed Arshad, Fatimah; Abd. Latif, Ismail (Federal Agricultural Marketing Authority (FAMA), 2011)
The importance of the retail sector to economic growth has been very significant. The rapid growth of the sector is partly contributed by the emergence of supermarkets and hypermarkets that are mostly foreign-owned. This has raised some concerns by the local conventional retailers including fresh fruit and vegetable (FFV) retailers. The government has reacted to the concerns by introducing new guidelines to developing new hypermarkets in this country. This study investigates the impacts of these two types of retailers on local FFV wholesalers and retailers. Data from personal interviews with FFV retailers and wholesalers were analysed. Results of the analyses showed that supermarkets and hypermarkets did impose competition on conventional wholesalers and retailers. However, they have also brought some changes to FFV retail business, such as promoting quality products, and a better and a systematic marketing approach.